Influence of customer reviews, safety and convenience on online purchasing decisions Case study marketplace shopee - Mistika Ignasia Br Ginting; Muinah fadhilah; Nonik Kusuma Ningrum (Universitas Muhammadiyah Makassar, 2023)
The purpose of the study was to determine the effect of customer reviews, security and convenience on online purchasing decisions through the marketplace. This research is a quantitative research. The target population is the people of Yogyakarta shopping online on the Shopee marketplace. The research sample is 100 respondents. The data collection method used the questionnaire method, while the data analysis technique used multiple regression analysis and classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. The results showed that customer reviews had a positive effect on online purchasing decisions with a significance value of 0.029 0.05. Security has a positive effect on online purchasing decisions with a significance value of 0.002 0.05. Ease has a positive effect on online purchasing decisions with a significance value of 0.000 0.05. Customer reviews, security and convenience simultaneously influence online purchasing decisions on the Shopee marketplace with a significance value of 0.000 0.05.